Lipoprotein apheresis is essential for managing pregnancies in patients with homozygous familial hypercholesterolemia: Seven case series and discussion. (November 2016) - Ogura, Masatsune; Makino, Hisashi; Kamiya, Chizuko; Yoshimatsu, Jun; Soran, Handrean; Eatough, Ruth; Perrone, Giuseppina; Harada-Shiba, Mariko; Stefanutti, Claudia
Abstract: Background and aims: For patients with homozygous familial hypercholesterolemia (HoFH), atherogenic lipoprotein changes and increased stress on cardiovascular system during pregnancy may pose substantial risk for both the mother and her fetus. Although lipoprotein apheresis (LA) is reported as the most effective therapy to control LDL-C levels during pregnancy in HoFH patients, only case reports have been published, and there is no guidance for management. Methods: We report twelve pregnancies and ten deliveries in seven patients with HoFH, and compare the clinical outcomes between patients who received LA during pregnancy and those who did not. Results: One patient who refused LA during pregnancy died from acute myocardial infarction after delivery. Another patient whose adherence to LA was poor also died of myocardial infarction during pregnancy. One patient who initiated LA at the age of 18 had to discontinue LA due to severe symptoms of angina pectoris during pregnancy. Another had symptoms of nausea, hypotension, and bradycardia with increased levels of serum bradykinin during a dextran sulfate cellulose absorption-based LA procedure. Although two of the other three patients had already had coronary artery disease by the time of pregnancy, early initiation of LA from childhood and good adherence to it during pregnancy resulted in the delivery of healthy infants without adverse effects. Conclusions: LA is essential for managing pregnancy safely in patients with HoFH. Increasing numbers of documented cases, including ours, will be helpful to guide future therapeutic decisions. Highlights: Lipoprotein apheresis (LA) is essential for managing pregnancy safely in homozygous familial hypercholesterolemia (HoFH). Patients who refused LA died of myocardial infarction. Good adherence to LA during pregnancy resulted in uneventful deliveries. Bradykinin-induced hypotension may occur during lipoprotein absorption. Increasing numbers of documented cases will be helpful to treat pregnant HoFH.